URANIUM MINING AND ASSOCIATED ENVIRONMENTAL PROBLEMS IN UKRAINE - Dudar, T.; Zakrytnyi, Ye.; Bugera, M. (Science-based technologies, 2015)
Nuclear power demands in uranium resources are expected to increase in the nearest future. So, the problem of uranium mining impact into the environment is a challenge and requires straightway actions. The tendencies in uranium mining in the world and in Ukraine for the period of 2003-2013 are considered in this paper. It is especially noted the increase in uranium raw material demands and as a consequence in its mining. The available and potential uranium resources are overviewed. It should be also noted that uranium ores in Ukraine are not considered to be rich; nevertheless they are able to meet the requirements of the domestic power plants. The prognosis calculations on uranium extraction volumes till 2017 are presented. It makes possible to assess the nuclear power industry potential in Ukraine and its competitive performance. A special focus was on the environmental impact as a result of the uranium mining, processing and enrichment. The following aspects were noted: tailings accumulation, large volumes of radioactive wastes, negative impact into the soils, underground and surface waters, contamination of the atmospheric air, occupational and community health. Questions on reduce and prevention of negative effects into the water, soil, and geological environment, into the atmospheric air as well as some aspects on legislation and logistics were briefly overviewed.